2019
DOI: 10.1111/rge.12220
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Luowei Orefield in Xidamingshan, Guangxi, China

Abstract: Many types of hydrothermal deposits (e.g. W, Bi, Pb, Zn, Ag) are confined by faults and hidden granodiorite in the Luowei Orefield in Xidamingshan, Guangxi, China. The orebodies in the Luowei W–Bi deposit are predominantly layered and distributed along bedding in sandstones of the Cambrian Xiaoneichong Formation. The orebodies in the Lujing Pb–Zn deposit are controlled mainly by west‐south‐west (WSW)‐trending faults, and those in the Fenghuangshan Ag deposit are controlled mainly by west‐north‐west (WNW)‐trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…However, during this phase, the ancient Pacific Plate was moving nearly parallel to the direction of extension, suggesting that the N-S extensional stress was unrelated to the subduction of the ancient Pacific Plate and may have been associated with the back-arc tectonic setting resulting from the northward subduction of the Neo-Tethys Plate [12]. Previous studies of structural deformation and basin formation have suggested that N-S extension or compression in South China may have commenced as early as the late Early Cretaceous, at ~100 Ma [16,59].…”
Section: Late Cretaceousmentioning
confidence: 99%
“…However, during this phase, the ancient Pacific Plate was moving nearly parallel to the direction of extension, suggesting that the N-S extensional stress was unrelated to the subduction of the ancient Pacific Plate and may have been associated with the back-arc tectonic setting resulting from the northward subduction of the Neo-Tethys Plate [12]. Previous studies of structural deformation and basin formation have suggested that N-S extension or compression in South China may have commenced as early as the late Early Cretaceous, at ~100 Ma [16,59].…”
Section: Late Cretaceousmentioning
confidence: 99%